A new species in the genus Styracaster (Echinodermata: Asteroidea: Porcellanasteridae) from hadal depth of the Yap Trench in the western Pacific - Zhang, Ruiyan; Zhou, Yadong; Lu, Bo; Wang, Chunsheng (Zootaxa, 2017)
Styracaster yapensis sp. nov. is reported from the Yap Trench in the western Pacific from hadal depths between 6377–6575 m, which is among the deepest known occurrence of a species in this genus. It is distinguished from other Styracaster species by its abactinal surface armature and rudimentary cribriform organs. This paper provides a description of the new species along with detailed photos. The intraspecific differences between the holotype and paratype of the new species are examined with molecular and morphological approaches.